KARAKTERISTIK BIOLOGI DAN LAJU EKSPLOITASI IKAN PELAGIS KECIL DI PERAIRAN UTARA JAWA - Aulia Maghfirotul Khatami; Yonvitner; Isdrajad Setyobudiandi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Fishery activities in the North Java sea are dominated by small pelagic fisheries that have an important role in fisheries development in Indonesia. Although the national potential of small pelagic fish has not been optimally utilized, in some areas the water utilization rate has exceeded the sustainable potential. The rate of exploitation is a key parameter in describing the utilization rate of small pelagic fish resources in water. This study aims to know the biological characteristics and rate of exploitation in some species of fish that became the main catch on pelagic fisheries in the waters of North Java. Six species of small pelagic fishes (bigeye scad, rainbow sardine, short mackerel, yellow-striped scad, yellowtail scad, and fringscale sardinella) caught in the waters of Northern Java have been overexploited. In general, the biological characteristics of each fish have shown that most small pelagic fish caught have not reached the size of the first gonad mature. Also, mackerel, tuna, and tembang are categorized as potentially high risk of catching, presumably from the fish size parameter and the number of operated fishing gear.